Microbial volatile communication in human organotypic lung models. Issue 1 (December 2017) - Barkal, Layla; Procknow, Clare; Álvarez-García, Yasmín; Niu, Mengyao; Jiménez-Torres, José; Brockman-Schneider, Rebecca; Gern, James; Denlinger, Loren; Theberge, Ashleigh; Keller, Nancy; Berthier, Erwin; Beebe, David
Abstract We inhale respiratory pathogens continuously, and the subsequent signaling events between host and microbe are complex, ultimately resulting in clearance of the microbe, stable colonization of the host, or active disease. Traditional in vitro methods are ill-equipped to study these critical events in the context of the lung microenvironment. Here we introduce a microscale organotypic model of the human bronchiole for studying pulmonary infection. By leveraging microscale techniques, the model is designed to approximate the structure of the human bronchiole, containing airway, vascular, and extracellular matrix compartments. To complement direct infection of the organotypic bronchiole, we present a clickable extension that facilitates volatile compound communication between microbial populations and the host model. UsingAspergillus fumigatus, a respiratory pathogen, we characterize the inflammatory response of the organotypic bronchiole to infection. Finally, we demonstrate multikingdom, volatile-mediated communication between the organotypic bronchiole and cultures ofAspergillus fumigatus andPseudomonas aeruginosa . There is a need for improved in vitro models of host-microbe interactions in the lung. Here, Barkal et al. present a microscale organotypic model of the human bronchiole for studying pulmonary infection, including volatile compound communication between microbial populations and host cells.